The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.23887/ijssb.v6i2.46719
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Entrepreneurial Self-Efficacy in Mediating the Effect of Entrepreneurship Education and Financial Support on Entrepreneurial Behavior

Abstract: In college, the willingness of students to start or run a business is still relatively low. This study aimed to analyze the role of entrepreneurial self-efficacy in mediating the effect of entrepreneurship education and financial support on entrepreneurial behavior. This research is a type of causality research. Data collection was continued by distributing questionnaires in Google Form to several WhatsApp groups. This study's population is active university students who already have online businesses in Bali.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 44 publications
0
0
0
2
Order By: Relevance
“…Self-efficacy is an important factor in determining the entrepreneurial mindset. As stated in (Dharmanegara et al, 2022), self-efficacy refers to a person's ability to control the environment in a given situation. Several studies have found that self-efficacy can influence other factors that contribute to social entrepreneurial intention (Chan, 2018;Hockerts, 2017b;Pacut, 2020b).…”
Section: Self-efficacy and Social Entrepreneurial Intentionsmentioning
confidence: 99%
“…Self-efficacy is an important factor in determining the entrepreneurial mindset. As stated in (Dharmanegara et al, 2022), self-efficacy refers to a person's ability to control the environment in a given situation. Several studies have found that self-efficacy can influence other factors that contribute to social entrepreneurial intention (Chan, 2018;Hockerts, 2017b;Pacut, 2020b).…”
Section: Self-efficacy and Social Entrepreneurial Intentionsmentioning
confidence: 99%
“…Wei et al, (2022) menyatakan bahwa salah satu pendekatan untuk meningkatkan efikasi diri adalah mempelajari lingkungan yang potensial. Sementara itu persepsi tentang lingkungan yang potensial dalam membangun kewirausahaan akan mengarah pada niat berwirausaha (Dharmanegara et al, 2022). Temuan penelitian ini mirip dengan penelitian Elnadi & Gheith, (2021) dengan hasil menunjukan bahwa efikasi diri kewirausahaan memediasi hubungan antara ekosistem kewirausahaan dan niat kewirausahaan.…”
Section: Gambar 1 Tingkat Pengangguran Terbuka Banyuwangiunclassified
“…Namun pendidikan kewirausahaan dapat mendorong munculnya intensi berwirausaha dengan melibatkan efikasi diri yang ada di kalangan mahasiswa. Hasil temuan ini relevan dan sesuai dengan temuan yang sudah ada yang mengemukakan bahwa efikasi diri mampu berperan sebagai variabel mediasi pada pengaruh pendidikan kewirausahaan terhadap intensi berwirausaha (Prastyaningtyas et al, 2019;Dharmanegara et al, 2022;Lubada et al 2021;Wardani & Nugraha, 2021).…”
Section: Peran Efikasi Diri Dalam Memediasi Hubungan Antara Pendidika...unclassified